Carbon 13 isotopes reveal limited ocean circulation changes between interglacials of the last 800 ka - Bouttes, Nathaëlle (PANGAEA, 2020)
We present a compilation of δ13C data to characterize the ocean circulation during the interglacials of the last 800 000 years. We selected 9 interglacials for which we have collected the available δ13C and δ18O values.
Keywords: Carbon isotopes; circulation; Interglacial; ocean